Isolation, total synthesis and quantification of caffeoylisocitric acid, a characteristic ingredient of the superfood amaranth. Issue 33 (16th August 2019) - Zhou, Tianyi; Ringbeck, Benedikt; Schebb, Nils Helge; Scherkenbeck, Jürgen
Abstract: Amaranth is regarded as a new "super-vegetable" in western countries, albeit it is consumed for centuries in Africa and Asia. In addition to common carotenoids, flavonoids and polyphenols, caffeoylisocitric acid has been described as amaranth type-specific secondary metabolite. Remarkably, nothing is known on biological effects of this specific polyphenol. Here we detail a concise, diastereoselective synthesis of caffeoylisocitric acid, deuterium-labelling studies and a quantitative determination of the caffeoylisocitric acid content of three different amaranth types. Graphical abstract: Image 1